EFEKTIVITAS DIGITAL MARKETING PADA MEREK SKINCARE LOKAL (BRAND X) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Jasmine Lailyya Ramadhani; Sugeng Hariadi; Joshi Maharani Wibowo (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the influence of social media content, influencer marketing, dan Electronic Word of Mouth (eWOM) on consumers’ purchasing decisions for a local skincare brand (Brand X) in Surabaya. This research employed a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 104 respondents selected using the snowball sampling technique. The data were analyzed using multiple liniear regression with IBM SPSS Statistics version 26. The results indicate that social media content, influencer marketing, dan Electronic Word of Mouth (eWOM) each have a positive and significant effect o purchasing decision. Simultaneously, the three independent variables also have a positive and significant effect on purchasing decisions. Among the variables, Electronics Word of Mouth (eWOM) has the strongest influence on purchasing decisions. Furthermore, the cofficient determination (R²) of 0.511 indicates that the independent variabel explain 51.1% of the variation in purchasing decision, while the remaining 48.9% is explained by other factors outside the research model.